Increasing The Awareness of Students at Montenegrin Universities About the Importance of Sustainable Development - Marija Jankovic (Journal of Sustainability Perspectives, 2023)
Today's ecological problems that threaten life on the planet, including global warming, loss of biodiversity, plastic pollution of seas and oceans, are largely unrecognized by individuals and communities. In this sense, scientific institutions should play a key role in developing awareness in the community, especially among students, about the consequences of pollution, the costs of pollution, in such a way as to adopt and promote "green" development policies. Today's "green" universities recognize the importance of this important global topic and develop questions about sustainable development through their studies and extracurricular activities, promote sustainability topics through marketing activities, adopting the very concept of sustainable development in continuity. Courses focused on "green" issues are introduced through the academic curricula. This paper aims to examine the level of awareness of university students in Montenegro about the implementation and level of adoption of "green" policy in university practices and offer ways to improve this concept. The work will represent a good basis for the improvement and adoption of the concept of "green" development at Montenegrin universities.